SYNTHESIS AND ANTIBACTERIAL ACTIVITY OF NOVEL 5-ARYLIDENE-2-IMINO-3-(2- PHENYL- 1,8-NAPHTHYRIDIN-3-YL)THIAZOLIDIN-4-ONES - KUNDENAPALLY, RAMALINGAM; DOMALA, RAMESH; BATHULA, SREENIVASULU (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: Nowadays, antimicrobial resistance represents one of the most significant challenges in the medical community. To overcome the problem, it requires the discovery of newer safe and effective molecules against infectious sickness. Synthesis and screening of 1,8-naphthyridines have attracted much attention over the decades since it plays a key role against the microorganisms. Methods: 1,8-naphthyridine based 5-arylidene derivatives of thiazolidinone (3a-i) has been achieved by the cyclization reaction of 2-chloro-N- (2-phenyl-1,8-naphthyridin-3-yl)acetamide (1) with potassium thiocyanate in acetone followed by its Knoevenagel condensation reaction with appropriate arylaldehydes in ethanol. All the resulting products were confirmed using spectral and physicochemical data. Antibacterial activity was performed against different bacterial strains by agar disc diffusion method using ciprofloxacin as standard. Results: Compound 3b showed tremendous antibacterial activity among all the tested compounds. Conclusions: This study provides several advantages such as shorter reaction times, clean product, and good yields. Most of the final products possessed moderate to excellent antibacterial activity.